High vibration frequency of soft tissue occurs during gait in power-trained athletes - Chen, C.-H.; Yang, W.-W.; Chen, Y.-P.; Chen, V. C.-F.; Liu, C.; Shiang, T.-Y. (Journal of Sports Sciences, 2021)
Muscles serve as a critical regulator of locomotion and damping, resulting in changes of soft tissue vibration. However, whether muscle fibre compositions of different individuals will cause different extents of soft tissue vibration during gait is unclear. Therefore, this study investigated the differences in lower extremity vibration frequencies among power-trained and non-power-trained athletes during walking and running. Twelve weightlifting athletes were assigned to the power-trained group and twelve recreational runners were assigned to the non-power-trained group. Accelerometers were used to detect soft tissue compartment vibration frequencies of the rectus femoris (RF) and gastrocnemius medialis (GMS) during walking and running. Results indicated that power-trained athletes, as compared to the non-power-trained, induced significantly (p < 0.05) higher vibration frequencies in their soft tissue compartments during walking and running. This suggests that power-trained athletes, who have higher ratios of fatigable fast-twitch muscle fibres, may have induced higher soft tissue compartment vibration frequencies. As a result, there is a likelihood that power-trained athletes may recruit more fatigable fast-twitch muscle fibres during muscle tuning, causing dysfunctions during prolonged exercises.